Struktur Kebahasaan dan Fungsi Retoris Uslūb Nidā’ dalam Al-Qur`an: Kajian Balāgah dan Tafsir - Musfirah Musfirah; Andi Miswar; Mardan Mardan (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This study examines uslūb nidā’ (the rhetorical vocative style) in the Qur`an, addressing two research questions: (1) what are the linguistic structural forms of uslūb nidā’ in the Qur`an, and (2) what are the rhetorical functions of uslūb nidā’ from the perspectives of balāghah and Qur`anic exegesis? The study adopts a qualitative approach through library research. Seven verses were purposively selected from a total of 527 nidā’ verses in the Qur`an based on three criteria: representativeness of nidā’ particles, variety of munādā (addressees), and diversity of rhetorical functions. Primary data were drawn from Qur`anic verses and major exegetical works, including al-Tahrīr wa al-Tanwīr, Rūh al-Ma'ānī, and al-Kasysyāf, and were analyzed using a descriptive-analytical method informed by balāghah and tafsīr frameworks. The findings reveal that the Qur`an consistently employs يَا and يَا أَيُّهَا as its primary vocative particles across varied structural patterns, including nidā’-amr-khabar, nidā’-amr-nahy, nidā’-khabar, and istifhām-nidā’-khabar. The rhetorical functions identified include tanbīh (attention-drawing), takrīm (dignification), talattuf (tenderness), takhwīf (instilling awe), ta'kīd (emphasis), and taqrīr wa ilzām (argumentative assertion). A comparative analysis further reveals that Meccan nidā’ tends to serve functions of takhwīf and barā'ah, whereas Medinan nidā’ is predominantly characterized by takrīm and normative tanbīh. These findings indicate that uslūb nidā’ constitutes a structured and contextually sensitive rhetorical system rather than a mere grammatical device, with practical implications for Arabic language pedagogy, exegetical methodology, and Islamic preaching discourse.